(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Textile in the industry thread again wrapping in the process thread tension stabilizing of devices elastic element that is springs characteristics research TW2 - D machines at Artsoft Holding​ in the example of of springs singleness coefficients experimental determined. Research as a result spring up to 32–33% of virginity was unevenness of the bobbins mass and density various to be main reason that proven. The spring time to pass with elasticity properties decrease analysis made.